COVID-19 and the beef market in Latin America: An impact assessment by supply and demand - Tejada Mejía, Daniela; Díaz, Manuel Francisco; Enciso, Karen; Junca Paredes, Jhon Jairo; Sandoval, Danny; Burkart, Stefan (Frontiers Media, 2022)
The impact of COVID-19 on agricultural markets, especially the beef market, represents one of the greatest food security challenges the world is facing in the post-pandemic era and, for this reason, has been widely documented. This study contributes to the literature through a comprehensive impact analysis of the effects of COVID-19 on both the demand and supply of beef in Latin America and thus provides valuable information for two of the most important links of the beef value chain. Robust econometric methods and a graphic analysis were used that give solidity to the investigation. The analysis used a data panel of supply and demand variables between 2018 and 2022 derived from the US Department of Agriculture. The results suggest that the beef market was strongly affected by the pandemic related health emergency, presenting decreases in both consumption and production. These effects are transitory, however, since the analysis of the post-pandemic data revealed that consumption and production return to normal and seem to grow until smoothing out over time.